Incidence and Pattern of Adverse Events in Pentavalent Vaccine Recipients in Pune, India - Patel, Barun Bhai; Pandya, Kapil Harish; Shrestha, Bikal; Kumar, Raj; Kotwal, Atul (Medical Journal of Shree Birendra Hospital, 2017)
Introduction: Safety monitoring of vaccines used in routine programmes on immunization is important in all settings. There is a lot of debate in the country about the relevance of the pentavalent vaccine in general and the Hib component in particular, in view of reports of deaths in children following immunization. This study was conducted to evaluate the incidence and profile of AEFI in children receiving pentavalent vaccine. Methods: A cohort study was conducted between May to Oct 2012, in a tertiary care hospital, Pune. Exposed groups received pentavalent vaccine, while the control received DPT or DPT + Hep B. Both the groups were followed up telephonically after 24 hr, 48 hr, 72 hr and 7 days following vaccination. 175 children in both groups were studied. Convenient sampling was done recruiting consecutive vaccinees till the sample size was achieved. Frequency, percentage, mean difference (T test) and chi square test was used to find association Results: 100 % children were institutional delivery. In controls, 80 % received DPT and Hep B, rest received only DPT. Fever was present in 76.2 % among exposed and 26.7% among non-exposed. Presence of fever after 1 day following immunization was significantly associated with exposed group (P=0.003). In 19 % exposed group fever continued for 2nd day. Other side effects included swelling (4.8 %) and reduced appetite (4.8 %) among exposed. Conclusion: Pentavalent vaccine does not increase the probability of deaths among the vaccines vis-a-vis nor receivers. The profile of AEFI among both the groups, except fever, is similar as far as frequency and severity is concerned.